Peer-learning in Young Learners English Speaking Tasks: An Ecological Analysis - Santi - Farmasari (Universitas Negeri Makassar, 2022)
The study examined English teachers’ agentive actions in a speaking assessment when utilizing students’ talks as model of responses to promote peer- learning. This instrumental case study views teacher agency on assessment from an ecological perspective, emphasizing the quality of teachers’ engagement in their environment. The study involved four primary English teachers teaching Year 5 and Year 6. The data were collected through classroom observations, audio-stimulated verbal recall interviews, and field notes. The data were analyzed thematically in nVivo12Pro software, where the themes were identified through the repetition of keywords. Co-coding, back-translation, and participant validation were employed to achieve the trustworthiness and reliability of the data. The study revealed that peer-learning was facilitated following the teachers’ understanding of their ecological contexts, i.e., the emerging problems during the assessment and the students’ assessment needs. The four teachers exercised their agentive actions by assigning the More-Proficient Students (MPS) to perform a speaking talk, from which the Less-Proficient Students (LPS) could learn, and utilized the MPS’ talks accordingly. The study findings strengthened the importance of teachers’ engagement with their ecological contexts when determining agentive actions. In addition, the study shows an interplay between theories of classroom-based assessment, teacher agency, and English for young language learners to promote peer-learning. This study has implications for relevant stakeholders about providing better supports for teachers exercising their agentive roles in facilitating students’ learning.